Formulasi Hand & Body Lotion Antioksidan Ekstrak Lulur Tradisional - Nutrisia Aquariushinta Sayuti; Indarto AS; Suhendriyo Suhendriyo (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Scrub, Lotion, Antioxidants. Turmeric (Curcuma domestica L), Temu giring (Curcuma heyneana), cinnamon bark (Cinnamomum Bumani (nees) BI), Kemuning Leaf (Murraya paniculata (L) Jack) and sandalwood (Santalum album) was often combined in the manufacture of scrubs. This research aims to make Hand & Body lotion formula (H & B Lotion) antioxidant containing traditional herbal extract from the botanicals fifth practical that efficacious, stable, safe and preferred by consumers. This research was true experimental research. The antioxidant activity test was used the immersion method against free radical diphenyl -2- 1.1 picrylhydrazyls, the protection ability test using invitro test while irritation test and hedonic tests conducted on volunteers. Emulsions that tested were containing a traditional herbal extract with a concentration of 0.5%, 1.0%, and 1.5%. This study concluded that the H & B Lotion was stable with emulsifier concentrations of 4.5% Tween 80, the difference in concentration of the extract didn’t affect the protection ability and the safety of the product but it affect significantly on the efficacy of antioxidants and aroma sensory parameters on hedonic test’s results, Optimal antioxidant activity in traditional herbal extract concentration of 1.5%. The best products based assessment hedonic test was H & B lotion with extract content of 1.0%